124k views
5 votes
Simplify the following expression: 4/ 1/4-5/2

A. -16/9
B. -4/3
C. 189/400
D. -100/601

User Dpmcmlxxvi
by
5.6k points

2 Answers

4 votes
4 / (1/4 - 5/2) =
4 / (1/4 - 10/4) =
4 / (-9/4) =
4 * -4/9 =
-16/9 <==
User Gruuuvy
by
5.6k points
6 votes

Answer:

Explanation:

Alright, lets get started.

The given expression is :


(4)/((1)/(4)-(5)/(2))

Two fractions are in subtraction so we need to make common denominator


(4)/((1)/(4)-(10)/(4))


(4)/((1-10)/(4))


(4)/((-9)/(4))


(4*4)/(-9)}


-(16)/(9) : Answer A

Hope it will help :)

User Eamonn Gahan
by
6.8k points